PROBLEMATIKA TARI MINANGKABAU DALAM DINAMIKA PERTUNJUKAN INDUSTRI HIBURAN - Indrayuda, Indra (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2014)
This article is part of a research that reveals the problems regarding the Minangkabau dances from West Sumatera province. The development of entertainment industry has influenced the public taste in choosing art performance. The Minangkabau dances are threatened as an entertaining art in West Sumatera because they are less interesting to the entertaining art fans. This research is qualitative. Data is collected through observation, interview, and documentation. The data is then analysed using ethnography and phenomenology. The result shows that there are various weaknesses of the Minangkabau dances in aspects of artistic, esthetic, technique, and packaging. The weaknesses are identified through its movements, performance structures, durations, costumes, make-ups, as well as the dancers’ skills and expressions. Besides, the Minangkabau dances are not yet managed professionally for marketing purpose. Key Word: Minangkabau dances, entertaining arts, entertaining industry